Using pRIFLE criteria for acute kidney injury in critically ill children - Rina Amalia C. Saragih; Jose M. Mandei; Irene Yuniar; Rismala Dewi; Sudung O. Pardede; Antonius Pudjiadi; Abdul Latief (Indonesian Pediatric Society, 2013)
Backgi-ound Incidence of acute kidney injury (AKI) in critically illchildren and its mortality rate is high. The lack of a uniform definitionfor AKI leads to failure in determining kidney injury, delayedtreatment, and the inability to generalize research results.Objectives To evaluate the pediatric RIFLE (pRIFLE) criteria (riskfor renal dysfunction, injury to the kidney, failure of kidney function,loss of kidney function, and end-stage renal disease) for diagnosingand following the clinical course of AKI in critically ill children. Wealso aimed to compare AKI severity on days 1 and 3 of pediatricintensive care unit (PICU) stay in critically ill pediatric patients.Methods This prospective cohort study was performed in PICUpatients. Urine output (UOP), serum creatinine (SCr) , andglomerular filtration rate on days 1 and 3 of PICU stay wererecorded. Classification of AKI was determined according topRIFLE criteria. We also recorded subjects' immune status,pediatric logistic organ dysfunction (PELOD) score, admissiondiagnosis, the use of vasoactive medications, diuretics, andventilators, as well as PICU length of stay and mortality.Results Forty patients were enrolled in this study. AKI wasfound in 13 patients (33%). A comparison of AKI severity onday 1 and day 3 revealed no statistically significant differences forattainment of pRIFLE criteria by urine output only (pRIFLfu0 p;P=0.087) and by both UOP and SCr (pRIFLEcr+uo p; P= 0.577).However, attainment of pRIFLE criteria by SCr only (pRIFLEcrlwas significantly improved between days 1 and 3 (P =0.026). Therewas no statistically significant difference in mortality or length ofstay between subjects with AKI and those without AKI.Conclusion The pRIFLE criteria is feasible for use in diagnosingand following the clinical course of AKI in critically ill children.